Musical Intervention: An Evolutionary Era in Dentistry: Life Sciences-Dentistry - Pathak, Ankita; Dhamande, Mithilesh; Sathe, Seema; Gujjelwar, Smruti (International Journal of Life Science and Pharma Research, 2024)
Patients feels anxious when facing an intrusive operation in a dental office. Such perceptions may be triggered by variouscircumstances, including a bizarre situation, lack of control, a sense of imminent danger, reliance on strangers, and being far fromdear ones and friends. One of the most serious problems in both children and adults is dental anxiety. Patients who are anxiousavoid going to the dentist and postpone their appointments. Mostly, these patients with dental phobia feel more anxious whilesitting in the waiting area. To manage these patients, a decrease in the waiting period is also one of the considerable options.Dental stress must be identified and alleviated for such patients to receive quality care. Dental care is regarded as an invasiveprocedure and causes dental anxiety. To treat such type of fear, various complementary therapies should be considered. Functionalrelaxation therapy is also used to distract the patient's mind. Through distraction and the promotion of a calm environmenteliminates stress, anxiety, and fear, music has a therapeutic effect. Various studies were reported in the literature that musicaltherapy has a significant impact on managing dental anxiety. Dental anxiety, which is a long-term mental handicap for patients, canbe managed by applying music therapy. The objectives of this review are to know the means that trigger dental anxiety and toknow how to manage it with musical intervention. This literature review aims to gain knowledge of musical intervention in an eraof dentistry to manage dental phobia. To conclude, the effect of musical therapy on patients suffering from dental anxiety thedynamics of musical therapy should be considered.